The PENGARUH PENGGANTIAN TEPUNG IKAN DENGAN TEPUNG DAUN KELOR DALAM KONSENTRAT TERHADAP METABOLIT DARAH TERNAK KAMBING YANG DIBERI PAKAN SILASE RUMPUT KUME DAN DAUN GAMAL (Effect of replacing fish meal by moringa leaf meal in the concentrate on blood..... - Maria F. Dj. Putri; Markus M. Kleden; Daud Amalo (Universitas Nusa Cendana, 2022)
This research aimed to evaluate the effect of replacing fish meal by moringa leaf meal in the concentrate on blood metabolite of goats fed silage of kume grass-gliriciadia leaf mixture. Four male kacang goats aged 1-1.5 year with average initial body weight of 21.14 ± 1.06 kg and coeficient variation 4.13 % were used in this experiment. The experimental design was a latin square consisting of 4 treatments and 4 periode as replication. The treatments were K0 = silage mixture of kume grass-gliricidia leaf + concentrate with containing 100% of fish meal; K25 = mixture silage of kume grass-gliricidia leaf + concentrate with containing 75% of fish meal and 25% of moringa leaf meal; K50 = mixture silage of kume grass-gliricidia leaf + concentrate with containing 50% of fish meal and 50% of moringa leaf meal; K75 = mixture silage of kume grass-gliricidia leaf + concentrate with containing 75% of fish meal and 25% of moringa leaf meal. Results showed that treatment had no effect (P>0,05) on blood glucose, ureum, cholesterol and total protein plasm. It can be concluded that moringa leaf meal can be used as fish meal replacement up to 75%.